VARIATIONS IN LEARNING METHODS; UPAYA DALAM MENCETAK PAKAR FIQH MELALUI PENGEMBANGAN PEMBELAJARAN KITAB KUNING DI MA’HAD ALY - Fathor Rozi (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2021)
This study aims to analyze the efforts to produce fiqh experts through the development of the yellow book at Ma'had Aly at Pondok Pesantren Salafiyah Syafi'iyah Sukorejo Situbondo. This research uses a qualitative approach, it is used to find more in-depth information about the efforts to produce fiqh experts through the development of the yellow book, while the type of research used is a case study that is focused on a particular case to be carefully observed and analyzed to completion. The results showed that: the efforts made by Ma'had Aly were using varied methods and models by combining (classical) Islamic boarding school learning methods such as sorogan, bandongan, wetonan, etc. and learning models in higher education (modern) such as active learning, demonstrations, CTL, Problem Based Intruction, etc. The supporting factors are the support of caregivers, lecturers of Ma'had Aly consisting of masyaikhs and a conducive environment, and the inhibiting factors are inadequate infrastructure and funds and the lack of focus of lecturers and supervisors in teaching at Ma'had Aly, Implications of developing the yellow book done by Ma'had Aly, it is possible that contemporary fiqh experts will be the successors of classical fuqaha.